The investigation of retinoic acid on spermatogenetic cell types of rats: Effect of retinoic acid on rat spermatogenic cells - Şentürk, Şengül; Sarıoğlu, Türkan; Köse, Timur; Uyanıkgil, Yiğit (Journal of Surgery and Medicine, 2024)
Background/Aim: Vitamin A is crucial for male fertility and the progression of the spermatogenetic process. Retinoic acid (RA), a metabolite of vitamin A, binds to three nuclear receptors, functioning similarly to a hormone by activating them. Our study aimed to investigate the effects of exogenous RA on spermatogenetic cell types, assessing them histochemically, immunohistochemically, and ultrastructurally. Methods: We used three groups: a control group and experimental groups treated with 40 mg/kg RA and 80 mg/kg RA. Each group contained eight adult Sprague-Dawley rats. RA, dissolved in corn oil, was administered to the experimental groups via gavage for 3 weeks. After 3 weeks, testes from the sacrificed animals were evaluated using light and electron microscopy. The sections were stained histochemically with hematoxylin-eosin (H&E) and periodic acid Schiff (PAS). Seminiferous tubules in the rats were staged using PAS staining. The cellular localization of the RARα receptor in the seminiferous tubules was identified after immunohistochemical analysis. Results: Immunoreactivity was qualitatively observed and graded from no staining to strong. In the immunohistochemical analysis, the experimental groups, particularly in stages VI, VII, VIII, and XIV, showed a significant difference in immunoreactivity compared to the control group. This difference was particularly evident in stage VI spermatogonia – the stage at which the first meiosis begins. A morphologically observed reduction in the seminiferous tubules, likely due to the loss of germ cells, was statistically significant in terms of the average diameter of the seminiferous tubules in the 80 mg/kg experimental group compared to both the control and the 40 mg/kg experimental group (P<0.001). Electron microscopic examination revealed an increase in intercellular distance, especially between basal compartment cells, in both experimental groups. Additionally, compared to the control group, both experimental groups showed an increase in the number of lipid-like granules on the membrane, particularly in the cytoplasm of spermatogonia and Sertoli cells. Conclusion: Based on our observations, this study suggests that exogenous RA can impact the overall histology of the testis. Moreover, it may play a significant role in the meiosis process by influencing the internal dynamics of spermatogenetic cell types.